Awareness and Acceptance Of Genetic Modified Food (GMF) Among The Malaysian Consumers - A.M.Z, Azlin; R, Baki; M.S.K , Enio; Abdullah, S. , J. Ho (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
The halal industry is growing vigorously to cater the Muslim consumers in Malaysia. The acceptance, awareness and perception towards the genetic modified food (GMF) is still insufficient to fulfil the Malaysian market and expectantly plays a major role in a long period. The purpose of this paper is to fill the knowledge gap to the study of GMF conducted in Malaysia. Qualitative data were collected via open-ended interview with four participants from various background namely Malaysian Agricultural Research and Development Institute (MARDI) researcher, P3, P4 and P1 by using single case and different site. All interviews were audio recorded, transcribed and analysed. Almost all participants familiar with the term genetic modified organism (GMO) or genetic modified food (GMF) which are two different entities but similar in biotechnology scope. Almost all participants were familiar with the term of genetic modified food. Since most of the participants came out with the science and biotechnology background, they perceived the GMF product but some of them did not trust of these products for various reasons. The participants agreed on the need for more information from a trusted and credible source that can easily access by the consumers. This study provides an in-depth insight into consumer’ awareness, perception and evaluation concerning the halalan toyyiban status of genetic modified food in Malaysia. The novelty of these finding could provide information for the biotechnology food industry to expand its market and develop its profitability and reliability to promo sustainable food production and consumption in the population.